Collaborative governance dalam Penanggulangan Banjir di Kota Dumai - Khairunsyah Purba; Rahmadani, Nelvi (POPULIKA, 2024)
Flood management in Dumai City is still not optimal so the intensity of the flooding that occurs is still quite high. On the other hand, flooding is a quite serious phenomenon and can cause impacts such as hampering community activities, causing economic losses both individually and generally, health problems and sometimes loss of life, and can damage the environment. The aim of this research is to determine government collaboration in dealing with floods that occurred in Dumai City. This research uses a literature review method. The informants in this research were the Dumai City Public Works and Spatial Planning Service, the Dumai City Regional Disaster Management Agency, the Dumai City Environmental Service, and the Riau Natural Resources Conservation Center. The results of this research show that through face-to-face dialogue with several meetings and long discussions, stakeholders are aware of the limitations of their authority, resulting in a division of tasks that can be carried out by each stakeholder. These main tasks and functions are stated in the signing of the cooperation agreement so that stakeholders focus on carrying out their own obligations to achieve effectiveness in flood management in Dumai City. On the other hand, there are still stakeholders who are incompetent in the collaboration process due to changes in positions so that the human resources owned by the agency do not know exactly what tasks they have to carry out. This causes delays in information being received by stakeholders, thereby hampering the coordination process in collaborating on flood management in Dumai City. Keywords: Flood; Collaborative Governance; Countermeasures.